Pupils’ First Experiences on Learning Adding Fractions on GeoGebra Applet (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2023)
GeoGebra is dynamic mathematics software that is utilized as an alternate learning media for studying Mathematics in the contemporary technology development period. Learning using GeoGebra can help students increase their knowledge of ideas and develop their mathematical thinking abilities. In this project, we apply a design research technique to create and test a GeoGebra exercise. The design study approach begins with the creation of GeoGebra-based activities on fraction addition by re-editing an existing GeoGebra design on the GeoGebra website and then testing it with five primary school students. Following the activity, we conducted interviews with students to determine the level of their comprehension of the idea of adding fractions. According to the findings of this study, pupils began to grasp and comprehend adding fractions since they could directly view how the fractions formed. However, some students continue to struggle with computer use owing to a lack of prior expertise.